Building Learning Culture Towards A Learning Organization to Empower Employee’s Knowledge - Maryani Maryani; Marihut Donna; Nilam Hapsari (ComTech: Computer, Mathematics and Engineering Applications, 2010)
This paper contains the application of knowledge management in PT Unilever to create a learning culture within the organization. Which consists of: knowledge sharing, informal sharing, online sharing and other sources. With the implementation of cultural sharing between employees, the module is already owned by PT Unilever as many as 250 modules. With the application of Knowledge Management PT Unilever awarded a global level, the Most Admired Knowledge Enterprise (MAKE) Award in the year 2005-2007 to the level of Indonesia and 2008 for the Asian level. In the end, knowledge-owned companies, creating a good performance by individuals or companies, and will create sustainable growth for the company. Sustainable growth is what is expected by the whole company in running its business activities.